Republic of Slovenia : Technical Assistance Report-Establishing a Spending Review Process. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses key findings and recommendations of the Technical Assistance report on establishing a spending review process in Slovenia. Slovenia's fragile fiscal situation requires further consolidation to ensure that the upward trajectory of public debt does not threaten long-term fiscal sustainability. Spending in the education sector is the fourth-highest spending level. Spending pressures also need to be explicitly identified, quantified, and included in the spending review to better inform the government's decision making process. There is also a need to update existing performance information associated with government expenditure programs to ensure that more meaningful information focused on achieving desired outcomes is developed to better inform future reviews.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet